Legitimacy challenges of local private 5G and beyond networks in Europe - Oxana Gisca; Marja Matinmikko-Blue; Petri Ahokangas; Seppo Yrjölä; Jillian Gordon (International Telecommunications Society (ITS), 2022)
Local 5G networks are on the agenda of public and private stakeholders, businesses, and policymakers. These local mobile communication networks can be deployed by different stakeholders to serve a variety of user groups with dexterous needs. Private networks serve closed user groups and have particularly attracted attention in many industrial use cases. The development and emergence of the local 5G and beyond networks depend on underlying regulations and implementation of the EU legal framework that varies between countries. The legal framework influencing local 5G network deployments and operations, which we here call the EU Digital Legal Framework, has been recently developed and some adopted by the EU, creating legitimacy challenges for local 5G and beyond network businesses. This influences especially deployments that are independent of mobile network operators (MNOs), impacting stakeholders' ability to become accepted and legitimate members of the mobile ecosystem. This paper identifies the relevant EU legal acts and presents the EU legal initiatives and a review of previous research from the perspective of legitimacy challenges of local private 5G and beyond networks. The study reveals the legal framework and pertinent elements to local 5G and beyond networks in Europe and the regulatory conditions under which new business models for local 5G and beyond networks may emerge. The analysis reviews the most recent legal acts relevant for the digital ecosystem and it adds to a better understanding of how regulation currently delimits the emerging business models of the local 5G and beyond networks. Finally, the paper highlights specific legitimacy challenges such as the lack of provisions for network architecture and tailored vertical-specific provisions on managing and ensuring the confidentiality of data that may humper the security and data privacy; absence of related legal provisions on spectrum design that currently are formed for wide-area mobile network operator networks; limited infrastructure planning and highly competitive approach between a private and public sector that cause challenges for access and infrastructure; absence of update of market analysis that may jeopardize the competition for local 5G and beyond networks. Moreover, it proposes future considerations to develop and promote a vision of local 5G and beyond networks, share best practices and tailored implementation mechanisms, develop bylaws and promote a harmonized approach in their implementation between the member countries, and promote social and ethical values by developing government support policies and apply a risk orientated approach regulatory intervention.
Keywords: 330